Analisis Pajak Penghasilan (PPh) Pasal 21 Coretax Atas Jasa Pelayanan Kapitasi Dokter Internship Puskesmas Ngronggot Tahun 2025 - Mariyah MARIYAH; Puji Rahayu (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the implementation of Coretax-based Income Tax (PPh) Article 21 on capitation services for non-ASN doctors (internship doctors) at the Ngronggot Community Health Center in 2025. The study used a qualitative descriptive approach with a case study design. Data were obtained through observation, interviews, and documentation of the management of capitation services and the withholding of PPh Article 21 during the period July–September 2025. The results indicate that non-ASN doctors are categorized as non-employees, therefore, the imposition of PPh Article 21 on capitation services uses a progressive rate in accordance with Article 17 of the Income Tax Law. The amount of PPh Article 21 withheld is in line with the gross income received by each doctor. The implementation of Coretax supports orderly tax administration through a more systematic and documented process of tax calculation, withholding, and reporting. The study's conclusions indicate that the application of Coretax-based Article 21 Income Tax on capitation services for non-ASN doctors at the Ngronggot Community Health Center complies with applicable tax regulations and reflects tax compliance in the primary healthcare sector.